Intercultural interactions in a New Zealand university : Pakeha and Asian perspectives : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy (Arts) in Sociology at Massey University - Brebner, Lian-Hong (Massey University, 2005)
Research on the phenomenon of intercultural contact in Western higher education has attracted the interest of a wide scope of academic disciplines. Psychologists and communication experts have underlined the inextricable link between positive friendship encounter with host students and well-being of sojourning students. Educationalists have also highlighted the impact of culturally diverse classrooms on the academic experience of both home and overseas students. Against this backdrop, the focus of my study is to offer some sociological observations on the intercultural contact phenomenon from the perspective of Pakeha and Asian international students in the New Zealand university context. The present study has adopted a qualitative approach using focus groups and in-depth interviews. Results from the current research underscore that growth in the export education sector has strengthened New Zealand economy but it has not necessarily enriched the socio-cultural arena of its higher institutions of learning. Instead, ethnic segregation of varying levels has become more apparent institutionally as a result of the strengthening subcultures within the Asian international student communities. The proliferation of ethnic enclaves has had significant social implications for both Pakeha and Asians. The research outcome also indicates that academic capitalism has dominated the agenda of New Zealand higher education. Hence, the task of promoting international understanding and global interdependence in New Zealand higher education has been relegated to the periphery in terms of issues to be addressed. These sociological trends demonstrate an antithesis of the objective of international education. The challenge, therefore, is for those responsible for managing higher education to review and renew its commitment towards the cultivation of intercultural global citizens.
Keywords: Social interaction; Intercultural communication; Cross-cultural orientation; Asian international students; University students